If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x(4x + -7) = 0 Reorder the terms: 2x(-7 + 4x) = 0 (-7 * 2x + 4x * 2x) = 0 (-14x + 8x2) = 0 Solving -14x + 8x2 = 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), '2x'. 2x(-7 + 4x) = 0 Ignore the factor 2.Subproblem 1
Set the factor 'x' equal to zero and attempt to solve: Simplifying x = 0 Solving x = 0 Move all terms containing x to the left, all other terms to the right. Simplifying x = 0Subproblem 2
Set the factor '(-7 + 4x)' equal to zero and attempt to solve: Simplifying -7 + 4x = 0 Solving -7 + 4x = 0 Move all terms containing x to the left, all other terms to the right. Add '7' to each side of the equation. -7 + 7 + 4x = 0 + 7 Combine like terms: -7 + 7 = 0 0 + 4x = 0 + 7 4x = 0 + 7 Combine like terms: 0 + 7 = 7 4x = 7 Divide each side by '4'. x = 1.75 Simplifying x = 1.75Solution
x = {0, 1.75}
| 8+p=9 | | -x-17=11-2x | | 3-v+3=1-4v+1 | | -66+x=9x+62 | | 16x+21=46-y | | -7=-7x-3(-x+17) | | G=7F+6 | | -34-8x=29-11x | | 79x^2-200x+125=0 | | x+7+3x=13+x | | 6(a-3)= | | 45-33x+33-44x=-45+33x-33+44x | | 11x-11=7x+12 | | 4j+4=6 | | 6y-5=3+4y | | 3x^2y^4+7x^2y^4-10x^4y^2= | | 3k+5-k=-9 | | -2x=160 | | 2((x-2)/2)=0 | | 2((x-2)/2) | | 45-33x+33-44=-45+33x-33+44x | | 3y-3=14 | | -7x-3+6x=-8x+9 | | 12x+18y=50 | | -10x+10x-10x= | | 7a+5(a-3)= | | 35=3(5+2x) | | 2/3s-1/3=s/6=5/3 | | d-2.8/.2=-14 | | -16+5n=-7(-6+8n)3 | | K+7=-1 | | 6x+9=87-10x |